2008 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--3430
|View full text |Cite
|
Sign up to set email alerts
|

A Competency Gap In The Comprehensive Design Education

Abstract: Vukica Jovanovic began her academic career in 2001 when she graduated at University of Novi Sad, majoring in Industrial Engineering and Management, Minor in Mechatronics, Robotics and Automation. She was working as Graduate Research and Teaching assistant and lectured various courses at departments of Industrial Engineering, Mechanical Engineering and Mechatronics from 2001 until 2006. She was an active member European organizing committee of student robotic contest Eurobot and chief of Eurobot organizing comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This is especially beneficial for universities with multi-or inter-disciplinary curricula, as it facilitates a common language and understanding of competencies acquired from courses from diverse disciplines. While previous studies identified competency gaps in education vis a vis job market to improve university curricula (Jovanovic and Tomovic, 2008), the significance of our study is that it specifically investigates design education at a university with an interdisciplinary curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially beneficial for universities with multi-or inter-disciplinary curricula, as it facilitates a common language and understanding of competencies acquired from courses from diverse disciplines. While previous studies identified competency gaps in education vis a vis job market to improve university curricula (Jovanovic and Tomovic, 2008), the significance of our study is that it specifically investigates design education at a university with an interdisciplinary curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted how professional competencies could be aligned to the attributes used in curriculum maps that link learning experiences and assessments to the intended learning outcomes (Oliver et al, 2007). Studies also identify competency gaps in the education of engineers based on skills required in practice, to develop new interventions (Jovanovic and Tomovic, 2008;Petrović and Pale, 2021).…”
Section: Learning Progression and Competency Benchmarking In Design E...mentioning
confidence: 99%
“…However, implementing active learning strategies in engineering curricula requires extensive time and resources [4]. Despite these challenges, educational institutions have adopted active learning to address the professional skills gap of engineering graduates [5] [6]. These strategies vary from abstracted simulations using consumer goods [7] to complex facilities using specialized equipment [8].…”
Section: Active Learningmentioning
confidence: 99%